Polycarbonate resin composition and molded article

The polycarbonate resin composition, featuring a specific blend of ethylene-α-olefin copolymer and styrene-based elastomer, addresses the issues of creaking noises, surface peeling, and self-tap performance in automotive components, providing enhanced durability and quiet operation in high-temperature conditions.

JP7659406B2Active Publication Date: 2025-04-09MITSUBISHI ENG PLASTICS CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2021030957
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-02-26
Publication Date
2025-04-09
Estimated Expiration
2041-02-26

AI Technical Summary

Technical Problem

Polycarbonate resin/ABS resin alloys used in automotive interior components tend to produce creaking noises due to thermal expansion and contraction, and may experience surface peeling and poor self-tap properties over time, especially in high-temperature environments.

Method used

A polycarbonate resin composition is developed, containing 55-90 parts by mass of polycarbonate resin, 10-45 parts by mass of graft copolymer, 2-15 parts by mass of ethylene-α-olefin copolymer with an MFR of 0.9 g/10 minutes or more, and 0.5-10 parts by mass of styrene-based elastomer, with a mass ratio of ethylene-α-olefin copolymer to styrene-based elastomer greater than 1.

Benefits of technology

The composition significantly reduces creaking noises, maintains excellent self-tap performance, and prevents surface peeling, making it suitable for long-term use in high-temperature automotive environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007659406000001
    Figure 0007659406000001
  • Figure 0007659406000002
    Figure 0007659406000002
  • Figure 0007659406000003
    Figure 0007659406000003
Patent Text Reader

Abstract

To provide a polycarbonate resin composition and a molded article which less generate squeak noise (noise), have no problem of surface peeling, and are also excellent in self-tapping property.SOLUTION: A polycarbonate resin composition is provided which contains 55-90 pts.mass of a polycarbonate resin (A) and 10-45 pts.mass of a graft copolymer (B) including an aromatic vinyl monomer component (b1), a vinyl cyanide monomer component (b2) and a diene-based rubbery polymer component (b3), the polycarbonate resin composition further contains with respect to 100 pts.mass of the total of the polycarbonate resin (A) and the graft copolymer (B), 2-15 pts.mass of an ethylene-α-olefin copolymer (C) having an MFR (measurement at 190°C and 21.18 N) of 0.9 g / 10 minutes or more, and 0.5-10 pts.mass of a styrenic elastomer (D), wherein a mass ratio (C) / (D) of a content of (C) to a content of (D) is more than 1.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polycarbonate resin composition and a molded article thereof, and more particularly to a polycarbonate resin composition and a molded article thereof which generate little creaking noise (abnormal noise), are free from the problem of surface peeling, and have excellent self-tapping properties. [Background technology]

[0002] Resin alloys in which ABS resin is blended with polycarbonate resin have excellent moldability, impact resistance, mechanical strength and heat resistance, and are therefore suitably used as parts and members of electric and electronic equipment such as vehicles, computers, notebook personal computers, various portable terminals, printers, copiers, and office automation and information equipment, etc. In particular, polycarbonate resin / ABS resin alloys have traditionally been widely used as interior materials in automobiles and the like for reasons such as ease of molding and weight reduction.

[0003] Products installed inside automobiles, such as displays, console panels, dashboards, car navigation systems, etc., are manufactured by fitting and assembling resin molded parts for the purpose of reducing weight. For example, when they have a housing structure, fitting parts for fitting are usually molded integrally at various locations on upper and lower halves of a molded part, and the housing molded product is manufactured by fitting the outer peripheries of the upper and lower molded parts together, with little or no use of screws, etc.

[0004] However, when such molded products are installed in a vehicle, the temperature in the vehicle cabin changes drastically from low to high, and the resin molded products are prone to deformation due to contraction and expansion caused by thermal fluctuations, and even slight deformation in the fitting parts makes it easy for creaking noises to occur due to vibrations while the vehicle is running. Creaking noises greatly reduce comfort when riding in a vehicle, and since luxury cars in particular require a higher level of interior quietness, preventing the occurrence of creaking noises is an extremely important issue.

[0005] However, molded articles made of polycarbonate resin / ABS resin alloys are prone to generating creaking noises (abnormal noises) when the molded articles come into dynamic contact with each other during vibration, etc. In order to reduce this creaking noise, it has been proposed to use AES resin instead of the ABS resin in the polycarbonate resin / ABS resin alloy (see Patent Document 1). However, products molded from alloys in which ABS resin is replaced with AES resin may be prone to squeaking noises when used for long periods of time in high-temperature environments. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2018-138680 A Summary of the Invention [Problem to be solved by the invention]

[0007] In addition, in order to fit and screw the molded parts together, they must have excellent self-tapping properties. Furthermore, since the appearance and texture of interior parts are important, it is also important that the molded products do not peel off from the surface. The object (purpose) of the present invention is to provide a polycarbonate resin composition and a molded article which generate little creaking noises (abnormal noises), generate little creaking noises (abnormal noises) even when used for long periods of time in high-temperature environments as vehicle parts, etc., and further have no problem of surface peeling and excellent self-tapping properties. [Means for solving the problem]

[0008] Means for Solving the Problems The present inventors have conducted extensive research in order to achieve the above object, and as a result have found that a polycarbonate resin composition comprising a polycarbonate resin / ABS resin alloy, which is rich in polycarbonate resin, an ethylene-α-olefin copolymer having an MFR of 0.9 g / 10 min or more, and a specific amount of a styrene-based elastomer, produces little creaking noise (abnormal noise), is free from the problem of surface peeling, and has excellent self-tapping properties, which has led to the completion of the present invention. That is, the present invention relates to the following polycarbonate resin composition and molded article.

[0009] 1. A method for producing a polycarbonate resin (A) comprising 55 to 90 parts by mass and a graft copolymer (B) comprising an aromatic vinyl monomer component (b1), a vinyl cyanide monomer component (b2) and a diene rubber polymer component (b3) in an amount of 100 parts by mass in total of (A) and (B), A polycarbonate resin composition comprising 2 to 15 parts by mass of an ethylene-α-olefin copolymer (C) having an MFR (measured at 190°C and 21.18 N) of 0.9 g / 10 min or more, and 0.5 to 10 parts by mass of a styrene-based elastomer (D), wherein the mass ratio (C) / (D) of the contents of (C) and (D) is greater than 1. 2. The polycarbonate resin composition according to 1 above, which has an abnormal noise risk index of 1 to 3 based on VDA203-206 of the German Association of the Automotive Industry. 3. The polycarbonate resin composition according to the above 1 or 2, wherein the graft copolymer (B) is an ABS resin. 4. A molded article obtained by molding the polycarbonate resin composition according to any one of 1 to 3 above. 5. The molded article according to claim 4, wherein the molded article is an automobile interior part. Effect of the Invention

[0010] The polycarbonate resin composition of the present invention generates little creaking noise (abnormal noise), generates little creaking noise (abnormal noise) even when used for a long time under a high temperature environment as a vehicle part, etc., has no problem of surface peeling, and has excellent self-tapping properties. Therefore, a molded product molded from the polycarbonate resin composition of the present invention can be particularly suitably used as an automobile interior part. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] The present invention will be described in detail below with reference to embodiments and examples, but the present invention is not limited to the embodiments and examples shown below. In this specification, the symbol "to" is used to mean that the numerical values ​​before and after it are included as the lower limit and upper limit.

[0012] The polycarbonate resin composition of the present invention is characterized in that it contains 55 to 90 parts by mass of a polycarbonate resin (A) and 10 to 45 parts by mass of a graft copolymer (B) containing an aromatic vinyl monomer component (b1), a vinyl cyanide monomer component (b2) and a diene rubber polymer component (b3) per 100 parts by mass of (A) and (B), and contains 2 to 15 parts by mass of an ethylene-α-olefin copolymer (C) having an MFR (measured at 190°C and 21.18N) of 0.9 g / 10 min or more and 0.5 to 10 parts by mass of a styrene-based elastomer (D), and the mass ratio (C) / (D) of the contents of (C) and (D) is greater than 1.

[0013] [Polycarbonate resin (A)] The polycarbonate resin (A) contained in the polycarbonate resin composition of the present invention is not limited in type, and may be used alone or in any combination of two or more kinds in any ratio. Polycarbonate resin is a polymer having a basic structure with a carbonate bond represented by the general formula: -[-OXOC(=O)-]-. In the above formula, X is generally a hydrocarbon, but X having a heteroatom or hetero bond may be used to impart various properties.

[0014] As the polycarbonate resin (A), particularly, an aromatic polycarbonate resin is preferable. The aromatic polycarbonate resin refers to a polycarbonate resin in which the carbons directly bonded to the carbonate bonds are aromatic carbons. Among various polycarbonates, the aromatic polycarbonate is superior in terms of heat resistance, mechanical properties, electrical properties, etc.

[0015] There is no restriction on the specific type of aromatic polycarbonate resin, but examples thereof include aromatic polycarbonate polymers obtained by reacting a dihydroxy compound with a carbonate precursor. In this case, in addition to the dihydroxy compound and the carbonate precursor, a polyhydroxy compound or the like may be reacted. A method of reacting carbon dioxide as a carbonate precursor with a cyclic ether may also be used. The aromatic polycarbonate polymer may be linear or branched. Furthermore, the aromatic polycarbonate polymer may be a homopolymer consisting of one type of repeating unit, or may be a copolymer having two or more types of repeating units. In this case, the copolymer may be selected from various copolymerization forms such as a random copolymer and a block copolymer. In addition, such an aromatic polycarbonate polymer is usually a thermoplastic resin.

[0016] Among the monomers that are raw materials for aromatic polycarbonate resins, examples of aromatic dihydroxy compounds include: Dihydroxybenzenes such as 1,2-dihydroxybenzene, 1,3-dihydroxybenzene (i.e., resorcinol), and 1,4-dihydroxybenzene;

[0017] Dihydroxybiphenyls such as 2,5-dihydroxybiphenyl, 2,2'-dihydroxybiphenyl, and 4,4'-dihydroxybiphenyl;

[0018] dihydroxynaphthalenes such as 2,2'-dihydroxy-1,1'-binaphthyl, 1,2-dihydroxynaphthalene, 1,3-dihydroxynaphthalene, 2,3-dihydroxynaphthalene, 1,6-dihydroxynaphthalene, 2,6-dihydroxynaphthalene, 1,7-dihydroxynaphthalene, and 2,7-dihydroxynaphthalene;

[0019] dihydroxydiaryl ethers such as 2,2'-dihydroxydiphenyl ether, 3,3'-dihydroxydiphenyl ether, 4,4'-dihydroxydiphenyl ether, 4,4'-dihydroxy-3,3'-dimethyldiphenyl ether, 1,4-bis(3-hydroxyphenoxy)benzene, and 1,3-bis(4-hydroxyphenoxy)benzene;

[0020] 2,2-bis(4-hydroxyphenyl)propane (i.e., bisphenol A), 1,1-bis(4-hydroxyphenyl)propane, 2,2-bis(3-methyl-4-hydroxyphenyl)propane (i.e., bisphenol C), 2,2-bis(3-methoxy-4-hydroxyphenyl)propane, 2-(4-hydroxyphenyl)-2-(3-methoxy-4-hydroxyphenyl)propane, 1,1-bis(3-tert-butyl-4-hydroxyphenyl)propane, 2,2-bis(3,5-dimethyl-4-hydroxyphenyl)propane, 2,2-bis(3-cyclohexyl-4-hydroxyphenyl)propane, 2-(4-hydroxyphenyl)-2-(3-cyclohexyl-4-hydroxyphenyl)propane, α,α'-bis(4-hydroxyphenyl)-1,4-diisopropylbenzene, 1,3-bis[2-(4-hydroxyphenyl)-2-propyl]benzene, bis(4-hydroxyphenyl)methane, Bis(4-hydroxyphenyl)cyclohexylmethane, Bis(4-hydroxyphenyl)phenylmethane, Bis(4-hydroxyphenyl)(4-propenylphenyl)methane, Bis(4-hydroxyphenyl)diphenylmethane, Bis(4-hydroxyphenyl)naphthylmethane, 1,1-bis(4-hydroxyphenyl)ethane, 1,1-bis(4-hydroxyphenyl)-1-phenylethane, 1,1-bis(4-hydroxyphenyl)-1-naphthylethan, 1,1-bis(4-hydroxyphenyl)butane, 2,2-bis(4-hydroxyphenyl)butane, 2,2-bis(4-hydroxyphenyl)pentane, 1,1-bis(4-hydroxyphenyl)hexane, 2,2-bis(4-hydroxyphenyl)hexane, 1,1-bis(4-hydroxyphenyl)octane, 2,2-bis(4-hydroxyphenyl)octane, 4,4-bis(4-hydroxyphenyl)heptane, 2,2-bis(4-hydroxyphenyl)nonane, 1,1-bis(4-hydroxyphenyl)decane, 1,1-bis(4-hydroxyphenyl)dodecane, Bis(hydroxyaryl)alkanes such as;

[0021] 1,1-bis(4-hydroxyphenyl)cyclopentane, 1,1-bis(4-hydroxyphenyl)cyclohexane, 1,1-bis(4-hydroxyphenyl)-3,3-dimethylcyclohexane, 1,1-bis(4-hydroxyphenyl)-3,4-dimethylcyclohexane, 1,1-bis(4-hydroxyphenyl)-3,5-dimethylcyclohexane, 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane, 1,1-bis(4-hydroxy-3,5-dimethylphenyl)-3,3,5-trimethylcyclohexane, 1,1-bis(4-hydroxyphenyl)-3-propyl-5-methylcyclohexane, 1,1-bis(4-hydroxyphenyl)-3-tert-butyl-cyclohexane, 1,1-bis(4-hydroxyphenyl)-4-tert-butyl-cyclohexane, 1,1-bis(4-hydroxyphenyl)-3-phenylcyclohexane, 1,1-bis(4-hydroxyphenyl)-4-phenylcyclohexane, Bis(hydroxyaryl)cycloalkanes such as;

[0022] 9,9-bis(4-hydroxyphenyl)fluorene, Cardo structure-containing bisphenols such as 9,9-bis(4-hydroxy-3-methylphenyl)fluorene;

[0023] 4,4'-dihydroxydiphenyl sulfide, Dihydroxydiaryl sulfides such as 4,4'-dihydroxy-3,3'-dimethyldiphenyl sulfide;

[0024] Dihydroxydiaryl sulfoxides such as 4,4'-dihydroxydiphenyl sulfoxide and 4,4'-dihydroxy-3,3'-dimethyldiphenyl sulfoxide;

[0025] 4,4'-dihydroxydiphenyl sulfone, dihydroxydiarylsulfones such as 4,4'-dihydroxy-3,3'-dimethyldiphenylsulfone; etc.

[0026] Among these, bis(hydroxyaryl)alkanes are preferred, and bis(4-hydroxyphenyl)alkanes are particularly preferred. In particular, from the standpoint of impact resistance and heat resistance, 2,2-bis(4-hydroxyphenyl)propane (i.e., bisphenol A) and 2,2-bis(3-methyl-4-hydroxyphenyl)propane (i.e., bisphenol C) are preferred. The aromatic dihydroxy compounds may be used alone or in any combination of two or more in any ratio.

[0027] Examples of monomers that can be used as raw materials for aliphatic polycarbonate resins include: alkanediols such as ethane-1,2-diol, propane-1,2-diol, propane-1,3-diol, 2,2-dimethylpropane-1,3-diol, 2-methyl-2-propylpropane-1,3-diol, butane-1,4-diol, pentane-1,5-diol, hexane-1,6-diol, and decane-1,10-diol;

[0028] Cycloalkanediols such as cyclopentane-1,2-diol, cyclohexane-1,2-diol, cyclohexane-1,4-diol, 1,4-cyclohexanedimethanol, 4-(2-hydroxyethyl)cyclohexanol, and 2,2,4,4-tetramethyl-cyclobutane-1,3-diol;

[0029] Glycols such as ethylene glycol, 2,2'-oxydiethanol (i.e., diethylene glycol), triethylene glycol, propylene glycol, spiroglycol, etc.;

[0030] aralkyldiols such as 1,2-benzenedimethanol, 1,3-benzenedimethanol, 1,4-benzenedimethanol, 1,4-benzenediethanol, 1,3-bis(2-hydroxyethoxy)benzene, 1,4-bis(2-hydroxyethoxy)benzene, 2,3-bis(hydroxymethyl)naphthalene, 1,6-bis(hydroxyethoxy)naphthalene, 4,4'-biphenyldimethanol, 4,4'-biphenyldiethanol, 1,4-bis(2-hydroxyethoxy)biphenyl, bisphenol A bis(2-hydroxyethyl)ether, and bisphenol S bis(2-hydroxyethyl)ether;

[0031] Examples of such cyclic ethers include 1,2-epoxyethane (i.e., ethylene oxide), 1,2-epoxypropane (i.e., propylene oxide), 1,2-epoxycyclopentane, 1,2-epoxycyclohexane, 1,4-epoxycyclohexane, 1-methyl-1,2-epoxycyclohexane, 2,3-epoxynorbornane, and 1,3-epoxypropane.

[0032] Among the monomers that are raw materials for polycarbonate resins, examples of carbonate precursors include carbonyl halides, carbonate esters, etc. The carbonate precursors may be used alone or in any combination and ratio of two or more.

[0033] Specific examples of carbonyl halides include phosgene; haloformates such as bischloroformates of dihydroxy compounds and monochloroformates of dihydroxy compounds; and the like. Specific examples of carbonate esters include diaryl carbonates such as diphenyl carbonate and ditolyl carbonate; dialkyl carbonates such as dimethyl carbonate and diethyl carbonate; biscarbonates of dihydroxy compounds, monocarbonates of dihydroxy compounds, and carbonates of dihydroxy compounds such as cyclic carbonates.

[0034] The method for producing the polycarbonate resin is not particularly limited, and any known method can be used, such as interfacial polymerization, melt transesterification, pyridine method, ring-opening polymerization of a cyclic carbonate compound, and solid-phase transesterification of a prepolymer.

[0035] The molecular weight of the polycarbonate resin (A) is arbitrary and may be appropriately selected and determined, but the viscosity average molecular weight [Mv] is preferably 10,000 to 40,000. If the viscosity average molecular weight is less than 10,000, the mechanical strength tends to be insufficient, and if the viscosity average molecular weight exceeds 40,000, the fluidity and moldability tend to be poor. The viscosity average molecular weight is more preferably 16,000 to 40,000, further preferably 18,000 to 30,000, and particularly 18,500 to 25,000. The molecular weight can be adjusted to such a range by a known method such as controlling the amount of a molecular weight regulator as described later.

[0036] Here, the viscosity average molecular weight [Mv] is calculated by using methylene chloride as a solvent, measuring the intrinsic viscosity [η] (unit: dl / g) at 25°C using an Ubbelohde viscometer, and calculating the viscosity average molecular weight [Mv] using the Schnell viscosity formula, i.e., η = 1.23 × 10 -4 Mv 0.83 The intrinsic viscosity [η] is calculated by measuring the specific viscosity [ηsp] at each solution concentration [C] (g / dl) and calculating it from the following formula:

number

[0037] Other matters regarding polycarbonate resin The terminal hydroxyl group concentration of the polycarbonate resin is arbitrary and may be appropriately selected and determined, but is usually 1,000 ppm or less, preferably 800 ppm or less, more preferably 600 ppm or less. In this way, the residence heat stability and color tone of the polycarbonate resin composition can be further improved. The lower limit is usually 10 ppm or more, preferably 30 ppm or more, more preferably 40 ppm or more, particularly for polycarbonate resins produced by the melt transesterification method. This can suppress the decrease in molecular weight and further improve the mechanical properties of the polycarbonate resin composition. The unit of the terminal hydroxyl group concentration is the mass of the terminal hydroxyl group relative to the mass of the polycarbonate resin, expressed in ppm. The measurement method is colorimetric determination using the titanium tetrachloride / acetic acid method (the method described in Macromol. Chem. 88 215 (1965)).

[0038] The polycarbonate resin (A) is not limited to an embodiment containing only one type of polycarbonate resin, and may be a mixture of two or more types of polycarbonate resins having different monomer compositions, molecular weights, terminal hydroxyl group concentrations, etc. Also, a polycarbonate resin may be mixed with another thermoplastic resin to be used as an alloy (mixture).

[0039] Furthermore, for example, the polycarbonate resin may be constituted as a copolymer mainly composed of polycarbonate resin, such as a copolymer with an oligomer or polymer having a siloxane structure for the purpose of further enhancing flame retardancy and impact resistance; a copolymer with a monomer, oligomer or polymer having a phosphorus atom for the purpose of further improving thermal oxidation stability and flame retardancy; a copolymer with a monomer, oligomer or polymer having a dihydroxyanthraquinone structure for the purpose of improving thermal oxidation stability; a copolymer with an oligomer or polymer having an olefin structure such as polystyrene for improving optical properties; or a copolymer with a polyester resin oligomer or polymer for the purpose of improving chemical resistance.

[0040] In order to improve the appearance and flowability of the molded product, the polycarbonate resin may contain a polycarbonate oligomer. The viscosity average molecular weight [Mv] of this polycarbonate oligomer is usually 1,500 or more, preferably 2,000 or more, and usually 9,500 or less, preferably 9,000 or less. Furthermore, the polycarbonate oligomer contained is preferably 30% by mass or less of the polycarbonate resin (including the polycarbonate oligomer).

[0041] Furthermore, the polycarbonate resin may be not only a virgin raw material, but also a polycarbonate resin regenerated from a used product (so-called material recycled polycarbonate resin). Examples of the used product include optical recording media such as optical disks; light guide plates; transparent vehicle components such as automobile window glass, automobile headlamp lenses, and windshields; containers such as water bottles; eyeglass lenses; soundproof walls, glass windows, corrugated sheets, and other building components. In addition, crushed products obtained from non-conforming products, sprues, runners, and the like, or pellets obtained by melting them, and the like, can also be used. However, the recycled polycarbonate resin is preferably 80% by mass or less, and more preferably 50% by mass or less, of the polycarbonate resin contained in the polycarbonate resin composition. Since the recycled polycarbonate resin is highly likely to have been deteriorated by heat degradation, aging degradation, etc., if such a polycarbonate resin is used in an amount greater than the above range, the hue and mechanical properties may be deteriorated.

[0042] [Graft copolymer (B) containing an aromatic vinyl monomer component (b1), a vinyl cyanide monomer component (b2) and a diene rubber polymer component (b3)] The graft copolymer (B) contained in the polycarbonate resin composition of the present invention is a graft copolymer containing an aromatic vinyl monomer component (b1), a vinyl cyanide monomer component (b2), and a diene rubber polymer component (b3). The graft copolymer (B) preferably comprises 40-80% by mass of the aromatic vinyl monomer component (b1), 10-30% by mass of the vinyl cyanide monomer component (b2), and 10-50% by mass of the diene rubber polymer component (b3), and may further contain 0-30% by mass of other monomer components (b4).

[0043] Examples of the aromatic vinyl monomer component (b1) in the graft copolymer (B) include styrene, α-methylstyrene, o-methylstyrene, p-methylstyrene, vinylxylene, ethylstyrene, dimethylstyrene, p-tert-butylstyrene, vinylnaphthalene, methoxystyrene, monobromostyrene, dibromostyrene, fluorostyrene, and tribromostyrene, with styrene being particularly preferred. The proportion of the aromatic vinyl monomer component (b1) in the graft copolymer (B) is preferably in the range of 40 to 80 mass%, more preferably 45 mass% or more, even more preferably 50 mass% or more, particularly preferably 55 mass% or more, and more preferably 75 mass% or less, even more preferably 70 mass% or less, particularly preferably 65 mass% or less, based on 100 mass% of the graft copolymer (B).

[0044] Examples of the vinyl cyanide monomer component (b2) in the graft copolymer (B) include acrylonitrile and methacrylonitrile, with acrylonitrile being particularly preferred. The proportion of the vinyl cyanide monomer component (b2) in the graft copolymer (B) is preferably in the range of 10 to 30 mass%, more preferably 12 mass% or more, even more preferably 14 mass% or more, particularly preferably 15 mass% or more, and more preferably 28 mass% or less, even more preferably 26 mass% or less, particularly preferably 25 mass% or less, based on 100 mass% of the graft copolymer (B).

[0045] As the diene rubbery polymer component (b3) of the graft copolymer (B), for example, a rubber component such as polybutadiene, polyisoprene, or styrene-butadiene copolymer is used. The proportion of the diene rubbery polymer component (b3) in the graft copolymer (B) is preferably in the range of 10 to 50 mass%, more preferably 13 mass% or more, even more preferably 14 mass% or more, particularly preferably 15 mass% or more, and more preferably 45 mass% or less, in 100 mass% of the graft copolymer (B).

[0046] Furthermore, it may be a copolymer of other monomer components (b4) copolymerizable with these. In this case, examples of the other copolymerizable vinyl monomers include maleimide-based monomers such as maleimide, N-methylmaleimide, N-cyclohexylmaleimide, and N-phenylmaleimide, acrylamide-based monomers such as acrylamide and N-methylacrylamide, unsaturated acid anhydrides such as maleic anhydride and itaconic anhydride, unsaturated acids such as acrylic acid and methacrylic acid, glycidyl acrylate, glycidyl methacrylate, 2-hydroxyethyl acrylate, 2-hydroxyethyl methacrylate, methoxypolyethylene glycol methacrylate, and the like. The proportion of the other monomer component (b4) in the graft copolymer (B) is preferably in the range of 0 to 30 mass%, more preferably 20 mass% or less, even more preferably 10 mass% or less, even more preferably 5 mass% or less, particularly preferably 3 mass% or less, and even more preferably 2 mass% or less, based on 100 mass% of the graft copolymer (B).

[0047] Specific preferred examples of the graft copolymer (B) include acrylonitrile-butadiene-styrene graft copolymer, acrylonitrile-butadiene-styrene-α-methylstyrene graft copolymer, acrylonitrile·ethylene-propylene-diene·styrene copolymer, etc., and among these, acrylonitrile-butadiene-styrene graft copolymer, acrylonitrile·ethylene-propylene-diene·styrene copolymer, in particular ABS resin and AES resin are preferred.

[0048] The graft copolymer (B) is usually produced by a method such as bulk polymerization, solution polymerization, suspension polymerization, or emulsion polymerization, and any of these methods can be used.

[0049] The content of the graft copolymer (B) is 10 to 45 parts by mass, preferably 12 parts by mass or more, more preferably 15 parts by mass or more, preferably 42 parts by mass or less, more preferably 40 parts by mass or less, based on 100 parts by mass of the total of the polycarbonate resin (A) and the graft copolymer (B). By having the content in such a range, the resin composition can have excellent heat resistance and fluidity. If the amount of the graft copolymer (B) exceeds 45 parts by mass, the heat resistance decreases, and if it is less than 10 parts by mass, the fluidity decreases.

[0050] [Ethylene-α-olefin copolymer (C)] The ethylene-α-olefin copolymer (C) contained in the polycarbonate resin composition of the present invention has an MFR (measured at 190° C. and 21.18 N) of 0.9 g / 10 min or more. In the present invention, by incorporating an ethylene-α-olefin copolymer (C) having such an MFR into an alloy of a polycarbonate resin (A) and a graft copolymer (B), the generation of squeak noises (abnormal noises) is reduced, and even when used for a long period of time under a high temperature environment as a vehicle part or the like, the generation of squeak noises (abnormal noises) is reduced. In addition, by combining with a styrene-based elastomer (D) at a specific content and amount ratio, a polycarbonate resin composition having excellent impact resistance and free from surface peeling can be obtained.

[0051] If the MFR is less than 0.9g / 10min, the impact resistance is reduced. Also, if the MFR is too high, the surface layer is easily peeled off, so the MFR is preferably 75g / 10min or less, more preferably 50g / 10min or less, even more preferably 40g / 10min or less, among which, preferably 30g / 10min or less, and is preferably 1g / 10min or more, more preferably 1.5g / 10min or more, among which, 2g / 10min or more, 3g / 10min or more, 4g / 10min or more are preferred, and particularly preferably 5g / 10min or more are preferred. The MFR is a melt flow rate (MFR) measured at a temperature of 190° C. under a load of 21.18 N in accordance with JIS K7210 (1995).

[0052] The density of the ethylene-α-olefin copolymer (C) is 0.940 g / cm 3It is preferable that the density is less than 0.940 g / cm. 3 If the density exceeds 0.935 g / cm, the crystallinity increases and the impact resistance tends to decrease. 3 More preferably, 0.930 g / cm 3 Below, 0.925g / cm 3 Below, 0.920g / cm 3 Below, especially 0.915g / cm 3 Below, especially 0.910g / cm 3 Below 0.908g / cm, most preferably 0.908g / cm 3 The following is the result. The density is preferably 0.800 g / cm 3 More preferably, 0.820 g / cm 3 More preferably, 0.840 g / cm 3 More preferably, 0.850 g / cm 3 Above, especially 0.860g / cm 3 More preferably, 0.870 g / cm 3 More preferably, 0.880 g / cm 3 That's all. The density of the ethylene-α-olefin copolymer (C) is a value measured in accordance with JIS K7112.

[0053] The ethylene-α-olefin copolymer (C) is a copolymer containing a monomer unit derived from ethylene and a monomer unit derived from an α-olefin. The α-olefin is preferably an α-olefin having 3 to 20 carbon atoms, such as propylene, 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene, 1-decene, 1-dodecene, 4-methyl-1-pentene, and 4-methyl-1-hexene. The copolymer may contain only one type of monomer unit derived from these α-olefins, or may contain two or more types. The α-olefin is preferably 1-butene, 1-hexene, 4-methyl-1-pentene, or 1-octene, and more preferably 1-butene or 1-hexene.

[0054] Examples of the ethylene-α-olefin copolymer (C) include ethylene-1-butene copolymer, ethylene-1-hexene copolymer, ethylene-4-methyl-1-pentene copolymer, ethylene-1-octene copolymer, ethylene-1-butene-1-hexene copolymer, ethylene-1-butene-4-methyl-1-pentene copolymer, ethylene-1-butene-1-octene copolymer, ethylene-1-hexene-1-octene copolymer, and the like, preferably ethylene-1-butene copolymer, ethylene-1-hexene copolymer, ethylene-4-methyl-1-pentene copolymer, ethylene-1-butene-1-hexene copolymer, ethylene-1-butene-1-octene copolymer, or ethylene-1-hexene-1-octene copolymer, particularly preferably ethylene-1-butene copolymer, ethylene-1-hexene copolymer.

[0055] In the ethylene-α-olefin copolymer (C), the content of monomer units derived from the α-olefin is preferably 1 to 49 mass%, more preferably 5 to 49 mass%, even more preferably 8 to 49 mass%, and particularly preferably 10 to 49 mass%, based on 100% total mass of the copolymer (C).

[0056] The ethylene-α-olefin copolymer (C) is preferably an ethylene-α-olefin copolymer obtained by polymerization using a polymerization catalyst such as a Ziegler catalyst, a vanadium catalyst, a Phillips catalyst, or a metallocene catalyst (also called a single-site catalyst), or produced by high-pressure radical polymerization. Examples of the polymerization method include liquid phase polymerization, slurry polymerization, gas phase polymerization, and high pressure ionic polymerization.

[0057] In particular, the ethylene-α-olefin copolymer (C) is preferably a copolymer obtained by copolymerizing ethylene and an α-olefin using a Ziegler-Natta catalyst. The Ziegler-Natta catalyst has a titanium compound, which may be trivalent and / or tetravalent, and an organoaluminum compound as a cocatalyst, and any known catalyst can be used as the Ziegler-Natta catalyst. The polymerization reaction is usually carried out at a polymerization temperature of 30 to 300°C and at atmospheric pressure or 3,000 kg / cm 2 The polymerization reaction is carried out under a polymerization pressure of 300 to 3,000 kg / cm in the presence or absence of a solvent, in a gas-solid, liquid-solid or homogeneous liquid phase. Preferably, the polymerization reaction is carried out at a polymerization temperature of 130 to 300°C, and a polymerization pressure of 300 to 3,000 kg / cm. 2 It is preferred that the polymerization be carried out in a high pressure bulk process under a polymerization pressure of 1000 MPa or less.

[0058] The MFR of the ethylene-α-olefin copolymer (C) can be adjusted by adding a molecular weight regulator such as hydrogen and polymerizing it. The amount of hydrogen added varies depending on the catalyst used and the production conditions. In general, the MFR tends to increase when the amount of hydrogen added is increased, so it is preferable to determine the amount of hydrogen added according to the desired MFR. Similarly, the density of the ethylene-α-olefin copolymer (C) varies depending on the catalyst used and the production conditions, but can be adjusted by the concentration of the α-olefin in the ethylene-α-olefin copolymer.

[0059] The content of the ethylene-α-olefin copolymer (C) is 2 to 15 parts by mass relative to 100 parts by mass in total of the polycarbonate resin (A) and the graft copolymer (B). With such a content, it is possible to obtain a resin composition that generates less creaking noise (abnormal noise) while maintaining mechanical properties such as impact resistance. The content of the ethylene-α-olefin copolymer (C) is preferably 2.5 parts by mass or more, more preferably 3 parts by mass or more, and preferably 14 parts by mass or less, more preferably 13 parts by mass or less, even more preferably 12 parts by mass or less, among which 11 parts by mass or less, particularly preferably 10 parts by mass or less.

[0060] [Styrene-based elastomer (D)] The polycarbonate resin composition of the present invention further contains a styrene-based elastomer (D). By containing the styrene-based elastomer (D) in combination with each of the above components, the resin composition has excellent impact resistance, particularly low-temperature impact resistance, and is therefore particularly suitable for use in automobile interior parts.

[0061] The styrene-based elastomer (D) is preferably a block copolymer containing a polymer block containing an aromatic vinyl compound unit and a block of a conjugated diene polymer or its hydrogenated product, or an isobutylene polymer block. It is preferable that the polymer block containing an aromatic vinyl compound unit constitutes a hard segment, and the block of a conjugated diene polymer or its hydrogenated product, or the isobutylene polymer block constitutes a soft segment. The styrene-based elastomer (D) is more easily compatible with the aromatic vinyl compound unit as the amount of the aromatic vinyl compound unit is larger, and the problem of surface peeling is less likely to occur. Therefore, the content of the aromatic vinyl compound in the styrene-based elastomer (D) is preferably in the range of 14 to 68 mass%.

[0062] The aromatic vinyl monomer is not particularly limited, but examples thereof include styrene, α-methylstyrene, o-methylstyrene, p-methylstyrene, pt-butylstyrene, 1,3-dimethylstyrene, lower alkyl-substituted styrene, vinylnaphthalene, indene, etc. These may be used alone or in combination of two or more. Among cholera, styrene is preferred.

[0063] The conjugated diene is not particularly limited, and examples thereof include 1,3-butadiene, isoprene, chloroprene, and 2,3-dimethyl-1,3-butadiene. These may be used alone or in combination of two or more. Among them, 1,3-butadiene and / or isoprene are preferable. In addition, in a polymer block mainly composed of a conjugated diene, hydrogenation may be performed or a vinyl-based compound other than the conjugated diene may be copolymerized. Examples of the vinyl-based compound other than the conjugated diene include methacrylic acid ester, acrylic acid ester, ethylene, 1-butene, pentene, hexene, and octene.

[0064] When the styrene-based elastomer (D) is a polymer block containing an aromatic vinyl compound unit and a polymer block of a conjugated diene polymer or a hydrogenated product thereof, the polymer block containing an aromatic vinyl compound unit preferably accounts for 5 to 70 mass %.

[0065] When the styrene-based elastomer (D) is a polymer block containing an aromatic vinyl compound unit and an isobutylene polymer block, the mass ratio thereof (isobutylene polymer block) / aromatic vinyl compound polymer block) is not particularly limited, but is preferably 95 / 5 to 60 / 40, and more preferably 90 / 10 to 65 / 35.

[0066] The MFR of the styrene-based elastomer (D) is, at a temperature of 230°C and a load of 2.16 kgf, preferably 0.05 to 100 g / 10 min, more preferably 0.05 to 70 g / 10 min, and even more preferably 0.05 to 50 g / 10 min, of which 0.05 to 30 g / 10 min, 0.05 to 20 g / 10 min, and particularly preferably 0.05 to 15 g / 10 min.

[0067] The content of the styrene-based elastomer (D) is 0.5 to 10 parts by mass relative to 100 parts by mass in total of the polycarbonate resin (A) and the graft copolymer (B), and is preferably 0.8 parts by mass or more, more preferably 1 part by mass or more, and is preferably 7 parts by mass or less, more preferably 5 parts by mass or less, even more preferably 4 parts by mass or less, of which 3 parts by mass or less, and particularly preferably 2 parts by mass or less.

[0068] In the present invention, the mass ratio (C) / (D) of the content of the copolymer (C) and the styrene-based elastomer (D) is set to be greater than 1. By setting the mass ratio at such a level, it is possible to obtain a polycarbonate resin composition that generates less creaking noise (abnormal noise), generates less creaking noise (abnormal noise) even when used for a long time under a high temperature environment, has excellent impact resistance, and is free from surface peeling. (C) / (D) is preferably 1.2 or more, more preferably 1.4 or more, preferably 10 or less, more preferably 8 or less, among which 7 or less, further 6 or less, and particularly preferably 5 or less.

[0069] [Stabilizer] The polycarbonate resin composition of the present invention preferably contains a stabilizer, and the stabilizer is preferably a phosphorus-based stabilizer or a phenol-based stabilizer.

[0070] Any known phosphorus stabilizer can be used as the phosphorus stabilizer. Specific examples include phosphorus oxoacids such as phosphoric acid, phosphonic acid, phosphorous acid, phosphinic acid, and polyphosphoric acid; metal acid pyrophosphates such as sodium acid pyrophosphate, potassium acid pyrophosphate, and calcium acid pyrophosphate; phosphates of Group 1 or Group 2B metals such as potassium phosphate, sodium phosphate, cesium phosphate, and zinc phosphate; organic phosphate compounds, organic phosphite compounds, and organic phosphonite compounds, with organic phosphite compounds being particularly preferred.

[0071] Examples of organic phosphite compounds include triphenyl phosphite, tris(mononylphenyl)phosphite, tris(mononyl / dinonyl phenyl)phosphite, tris(2,4-di-tert-butylphenyl)phosphite, monooctyl diphenyl phosphite, dioctyl monophenyl phosphite, monodecyl diphenyl phosphite, didecyl monophenyl phosphite, tridecyl phosphite, trilauryl phosphite, tristearyl phosphite, and 2,2-methylenebis(4,6-di-tert-butylphenyl)octyl phosphite. Specific examples of such organic phosphite compounds include "ADK STAB 1178", "ADK STAB 2112", and "ADK STAB HP-10" manufactured by ADEKA CORPORATION, "JP-351", "JP-360", and "JP-3CP" manufactured by Johoku Chemical Industry Co., Ltd., and "IRGAFOS 168" manufactured by BASF. The phosphorus-based stabilizer may be contained either as one type or as two or more types in any combination and ratio.

[0072] The content of the phosphorus-based stabilizer is usually 0.001 parts by mass or more, preferably 0.01 parts by mass or more, more preferably 0.03 parts by mass or more, and usually 1 part by mass or less, preferably 0.7 parts by mass or less, more preferably 0.5 parts by mass or less, based on 100 parts by mass of the total of the polycarbonate resin (A) and the graft copolymer (B). If the content of the phosphorus-based stabilizer is less than the lower limit of the above range, the thermal stabilization effect may be insufficient, and if the content of the phosphorus-based stabilizer is more than the upper limit of the above range, the effect may plateau and become uneconomical.

[0073] The phenol-based stabilizer includes, for example, a hindered phenol-based antioxidant. Specific examples thereof include pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, thiodiethylene bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], N,N'-hexane-1,6-diylbis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionamide], 2,4-dimethyl-6-(1-methylpentadecyl)phenol, diethyl[[3,5-bis(1,1-dimethylethyl)-4-hydroxyphenyl]methyl]phosphonate, 3,3',3",5,5',5"-hexa-tert-butyl-a,a',a"-(mesitylene-2,4,6- triyl)tri-p-cresol, 4,6-bis(octylthiomethyl)-o-cresol, ethylene bis(oxyethylene)bis[3-(5-tert-butyl-4-hydroxy-m-tolyl)propionate], hexamethylene bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], 1,3,5-tris(3,5-di-tert-butyl-4-hydroxybenzyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, 2,6-di-tert-butyl-4-(4,6-bis(octylthio)-1,3,5-triazin-2-ylamino)phenol, 2-[1-(2-hydroxy-3,5-di-tert-pentylphenyl)ethyl]-4,6-di-tert-pentylphenyl acrylate, and the like.

[0074] Among them, pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] and octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate are preferred.Specific examples of such phenol-based antioxidants include "Irganox 1010" and "Irganox 1076" manufactured by BASF, and "Adeka STAB AO-50" and "Adeka STAB AO-60" manufactured by ADEKA. The phenol-based stabilizer may be contained either as one type or as two or more types in any combination and ratio.

[0075] The content of the phenolic stabilizer is usually 0.001 parts by mass or more, preferably 0.01 parts by mass or more, and usually 1 part by mass or less, preferably 0.5 parts by mass or less, based on 100 parts by mass of the total of the polycarbonate resin (A) and the graft copolymer (B). By making the content of the phenolic stabilizer equal to or more than the lower limit of the above range, the effect as a phenolic stabilizer can be sufficiently obtained. In addition, by making the content of the phenolic stabilizer equal to or less than the upper limit of the above range, the effect does not plateau, and it is economical.

[0076] [Release agent] The polycarbonate resin composition of the present invention preferably contains a release agent (lubricant). Examples of the release agent include aliphatic carboxylic acids, esters of aliphatic carboxylic acids and alcohols, aliphatic hydrocarbon compounds having a number average molecular weight of 200 to 15,000, and polysiloxane-based silicone oils.

[0077] Examples of the aliphatic carboxylic acid include saturated or unsaturated aliphatic mono-, di- or tri-carboxylic acids. Here, the aliphatic carboxylic acid also includes alicyclic carboxylic acids. Among these, preferred aliphatic carboxylic acids are mono- or di-carboxylic acids having 6 to 36 carbon atoms, and more preferred are saturated aliphatic mono-carboxylic acids having 6 to 36 carbon atoms. Specific examples of such aliphatic carboxylic acids include palmitic acid, stearic acid, caproic acid, capric acid, lauric acid, arachic acid, behenic acid, lignoceric acid, cerotic acid, melissic acid, tetralinic acid, montanic acid, adipic acid, and azelaic acid.

[0078] The aliphatic carboxylic acid in the ester of aliphatic carboxylic acid and alcohol can be, for example, the same as the aliphatic carboxylic acid. On the other hand, the alcohol can be, for example, a saturated or unsaturated monohydric or polyhydric alcohol. These alcohols may have a substituent such as a fluorine atom or an aryl group. Among these, a monohydric or polyhydric saturated alcohol having 30 or less carbon atoms is preferred, and an aliphatic saturated monohydric alcohol or an aliphatic saturated polyhydric alcohol having 30 or less carbon atoms is more preferred. Here, the term aliphatic is used to include alicyclic compounds.

[0079] Specific examples of such alcohols include octanol, decanol, dodecanol, stearyl alcohol, behenyl alcohol, ethylene glycol, diethylene glycol, glycerin, pentaerythritol, 2,2-dihydroxyperfluoropropanol, neopentylene glycol, ditrimethylolpropane, and dipentaerythritol.

[0080] The above ester may contain an aliphatic carboxylic acid and / or alcohol as an impurity. The above ester may be a pure substance, or may be a mixture of a plurality of compounds. The aliphatic carboxylic acid and alcohol that are combined to form an ester may each be one type, or two or more types may be used in any combination and ratio.

[0081] Specific examples of esters of aliphatic carboxylic acids and alcohols include beeswax (a mixture mainly composed of myricyl palmitate), stearyl stearate, behenyl behenate, stearyl behenate, glycerin monopalmitate, glycerin monostearate, glycerin distearate, glycerin tristearate, pentaerythritol monopalmitate, pentaerythritol monostearate, pentaerythritol distearate, pentaerythritol tristearate, and pentaerythritol tetrastearate.

[0082] Examples of aliphatic hydrocarbons having a number average molecular weight of 200 to 15,000 include liquid paraffin, paraffin wax, microwax, polyethylene wax, Fischer-Tropsch wax, and α-olefin oligomers having 3 to 12 carbon atoms. The aliphatic hydrocarbons also include alicyclic hydrocarbons. These hydrocarbons may be partially oxidized. Among these, paraffin wax, polyethylene wax, or a partial oxide of polyethylene wax is preferred, and paraffin wax and polyethylene wax are more preferred. The number average molecular weight of the aliphatic hydrocarbon is preferably 5,000 or less. The aliphatic hydrocarbon may be a single substance, but even if it is a mixture of substances having various constituent components and molecular weights, it is preferable that the main component is within the above range.

[0083] Examples of polysiloxane-based silicone oils include dimethyl silicone oil, methylphenyl silicone oil, diphenyl silicone oil, and fluorinated alkyl silicone.

[0084] The above-mentioned release agents may be contained alone or in any combination and ratio of two or more kinds.

[0085] The content of the release agent is usually 0.001 parts by mass or more, preferably 0.01 parts by mass or more, and usually 2 parts by mass or less, preferably 1 part by mass or less, based on 100 parts by mass of the total of the polycarbonate resin (A) and the graft copolymer (B). By making the content of the release agent equal to or more than the lower limit of the above range, it is easy to obtain a sufficient effect of releasability, and by making the content of the release agent equal to or less than the upper limit of the above range, sufficient hydrolysis resistance is obtained and mold contamination during injection molding is less likely to occur.

[0086] [Other ingredients] The polycarbonate resin composition of the present invention may contain other components in addition to those described above, as necessary, as long as the desired physical properties are not significantly impaired. Examples of the other components include other resins other than the polycarbonate resin (A), the graft copolymer (B), the ethylene-α-olefin copolymer (C), and the styrene-based elastomer (D), various resin additives, etc. The other components may be contained alone or in any combination and ratio of two or more.

[0087] Other resins include, for example, thermoplastic polyester resins such as polyethylene terephthalate resin, polytrimethylene terephthalate resin, and polybutylene terephthalate resin; styrene-based resins such as polystyrene resin, high impact polystyrene resin (HIPS), and acrylonitrile-styrene copolymer (AS resin); polyolefin resins such as polyethylene resin and polypropylene resin; polyamide resins; polyimide resins; polyetherimide resins; polyurethane resins; polyphenylene ether resins; polyphenylene sulfide resins; polysulfone resins; polymethacrylate resins, and the like. The other resins may be contained either alone or in any combination and ratio of two or more kinds.

[0088] When resins other than the above (A) to (D) are contained, the content thereof is preferably 20 parts by mass or less, more preferably 10 parts by mass or less, even more preferably 5 parts by mass or less, and particularly preferably 3 parts by mass or less, per 100 parts by mass of the total of the polycarbonate resin (A) and the graft copolymer (B).

[0089] Examples of resin additives other than those mentioned above include ultraviolet absorbers, dyes and pigments (including titanium oxide and carbon black), antistatic agents, fillers, flame retardants, antifogging agents, antiblocking agents, flow improvers, plasticizers, dispersants, and antibacterial agents. The other resin additives may be contained either as one type or as two or more types in any combination and ratio.

[0090] [Production of polycarbonate resin composition] There is no limitation on the method for producing the polycarbonate resin composition of the present invention, and a wide variety of known methods for producing polycarbonate resin compositions can be used, including a method in which the above-mentioned components (A) to (D) and other components to be mixed as necessary are mixed in advance using various mixers such as a tumbler or a Henschel mixer, and then melt-kneaded using a mixer such as a Banbury mixer, a roll, a Brabender, a single-screw kneading extruder, a twin-screw kneading extruder, a kneader, etc. The temperature for melt-kneading is not particularly limited, but is usually in the range of 240 to 320°C.

[0091] The polycarbonate resin composition of the present invention has high fluidity, excellent impact resistance, and heat resistance, a low coefficient of friction, little generation of abnormal noise, and excellent surface peeling resistance and self-tapping property. The polycarbonate resin composition of the present invention preferably has a risk of noise (RPN) in the range of 1 to 3, and particularly preferably 1, based on VDA203-206 of the German Association of the Automotive Industry. The dynamic friction coefficient based on the German Automotive Industry Association standard VDA230-206 is preferably in the range of 0.10 to 0.45 at 10N, 1 mm / s and 10N, 4 mm / s, and the static friction coefficient is preferably in the range of 0.10 to 0.45 at 10N, 1 mm / s and 10N, 4 mm / s. Since it has excellent surface peeling resistance, it is preferable that the evaluation score in the cross-cut test (cross-cut test) according to JIS K5400 is 8 points or more. Since the self-tapping property is excellent, the self-tapping breaking torque is preferably 0.81 to 1.50 Nm. Since it has excellent fluidity, it is preferable that the MVR is 4 to 20 g / 10 min at a temperature of 250° C. and a load of 2.16 kgf in accordance with ISO1133. The notched Charpy strength at 23°C according to ISO standard 179 is 40-90kJ / m 2 It is preferable that: Since it has excellent heat resistance, it is preferable that the DTUL (deflection temperature under load) based on ISO75-1 and ISO75-2 is 90 to 120°C. The specific details of each of the above measuring methods are as described in the Examples.

[0092] [Molded body] There is no limitation on the method of producing a molded body from the obtained resin composition pellets, and any molding method generally used for polycarbonate resin compositions can be used. Examples include injection molding, ultra-high speed injection molding, injection compression molding, two-color molding, gas-assisted and other hollow molding methods, molding using a heat-insulating mold, molding using a rapid heating mold, foam molding (including supercritical fluid), insert molding, and IMC (in-mold coating molding) molding. In view of ease of molding and productivity, injection molding and injection compression molding are preferred.

[0093] Molded articles made from the polycarbonate resin composition produce little creaking noises (abnormal noises), produce little creaking noises (abnormal noises) even when used for long periods of time in high-temperature environments, have no problems with surface peeling, and have excellent self-tapping properties. Therefore, the molded articles made from the polycarbonate resin composition of the present invention can be suitably used as parts that come into contact with each other or with other molded articles, such as parts in the automotive field, the OA equipment field, home appliances, and the electrical and electronic fields, and can be particularly suitably used as automotive interior parts.

[0094] When the molded product of the polycarbonate resin composition of the present invention is used as an automobile interior part, it is possible to significantly reduce the generation of creaking noise when the parts come into contact with each other or with other parts due to the vibration of the automobile. Examples of such automobile interior parts include in-car displays, car navigation systems, car audio systems, dashboards, instrument panels, overhead consoles, door trims, roof trims, switch panels, door linings, decoration panels, indicator panels, pillar garnishes such as front pillar garnishes, center pillar upper garnishes, rear pillar garnishes, cowl side garnishes, front and rear side garnishes, and center pillar lower garnishes, pillar trims, center consoles, console boxes, inner panels, door pockets, armrest bases, grab rails, assist grips, column covers, ventilators, ducts, air conditioners, switch parts, cup holders, sub-trunks, glove boxes, trunk side trims, trunk side linings, tailgate linings, and rear panels. EXAMPLES

[0095] The present invention will now be described with reference to examples. The raw material components used in the examples and comparative examples are as shown in Table 1 below. The MFR of the ethylene-α-olefin copolymer (C) is a value measured at a temperature of 190° C. under a load of 21.18 N, and the MFR of the styrene-based elastomer (D) is a value measured at a temperature of 230° C. under a load of 2.16 kgf.

[0096] [Table 1]

[0097] [Examples 1 to 20, Comparative Examples 1 to 8] The components shown in Table 1 were blended in the ratios (mass ratios) shown in Tables 3 to 5 below, and mixed uniformly in a tumbler to obtain a mixture. This mixture was fed to a twin-screw extruder (Toshiba Machine Co., Ltd., "TEM26SX"), kneaded under conditions of a screw rotation speed of 150 rpm, a discharge rate of 25 kg / hour, and a barrel temperature of 260°C, and extruded in the form of strands from the tip of the extrusion nozzle. The strands were quenched in a water bath, cut and pelletized using a pelletizer, and pellets of a polycarbonate resin composition were obtained.

[0098] <mvr> The pellets obtained by the above method were dried at 100° C. for 5 hours, and then the MVR (melt volume rate, unit: g / 10 min) was measured in accordance with ISO1133 at a measurement temperature of 250° C. and a load of 2.16 kgf.

[0099] <Charpy notched strength> The pellets obtained by the above method were dried at 100°C for 5 hours, and then injection molded using an injection molding machine (Nissei Plastic Industrial Co., Ltd., "NEX80III") at a cylinder temperature of 260°C and a mold temperature of 60°C to produce ISO multipurpose test pieces (3 mmt). Using the obtained ISO multipurpose test piece (3 mmt), the notched Charpy strength (unit: kJ / m) was measured at a temperature of 23°C based on ISO standard 179. 2 ) was measured.

[0100] <Heat resistance DTUL (temperature deflection under load)> The pellets obtained by the above method were dried at 100°C for 5 hours, and then injection molded using an injection molding machine (Nissei Plastic Industrial Co., Ltd., "NEX80III") under conditions of a cylinder temperature of 260°C, a mold temperature of 60°C, and a molding cycle of 45 seconds to obtain ISO multipurpose test pieces (4 mmt). Based on ISO75-1 and ISO75-2, a constant bending load (1.80 MPa) was applied in the flatwise direction to the centre of a 4 mm x 10 mm ISO multipurpose test piece (4 mmt), the temperature was raised at a constant rate, and the temperature (unit: °C) was measured when the strain at the centre reached 0.34 mm.

[0101] <Dynamic friction coefficient, static friction coefficient, creaking noise evaluation (Risk of abnormal noise: RPN)> The pellets obtained by the above method were injection molded using a Toshiba Machine Co., Ltd. injection molding machine "EC50SXII" under conditions of a cylinder temperature of 260°C and a mold temperature of 60°C to obtain a molded product (large test piece) with a length of 60 mm, a width of 60 mm, and a thickness of 3 mm. Separately, small test pieces with a length of 50 mm, a width of 25 mm, and a thickness of 3 mm were cut out from the large test piece with a disc saw. Next, the ends of the test pieces were chamfered with sandpaper with a grit size of #100, and then fine burrs were removed with a cutter knife to obtain small test pieces for creaking noise evaluation.

[0102] The large and small test pieces for evaluation were left in a thermostatic chamber at 85°C for 400 hours (heat treatment), and then cooled at 25°C for 24 hours to obtain heat-treated test pieces for evaluation. The obtained large test piece was set on the movable stage of a Ziegler stick-slip tester SSP-04, and the small test piece was set on the fixed stage. Under the conditions of a temperature of 23°C, a humidity of 50% RH, and the load (N) and speed (mm / sec) listed in Tables 3 to 5, the dynamic friction coefficient and static friction coefficient when rubbed three times with an amplitude of 20 mm, and the abnormal sound risk index (also called abnormal sound generation risk, RPN) were measured based on the German Automotive Industry Association standard VDA230-206. The abnormal sound risk index (RPN) is displayed on a 10-point scale from 1 to 10 by this device. The smaller the abnormal sound risk index value, the less likely it is to cause a squeak sound, and the larger it is, the more likely it is to cause a squeak sound. According to the German Association of the Automotive Industry standard VDA230-206, if the abnormal noise risk index is between 1 and 3, the risk of creaking noise is low and the product is considered to be at an acceptable level for practical use.

[0103] The obtained risk index of abnormal noise (RPN) was judged according to the following criteria A to C. A: The highest abnormal noise risk index under the tested conditions is 1 to 3. B: The highest abnormal noise risk index under the tested conditions is 4 to 5. C: The highest abnormal noise risk index under the tested conditions is 6 to 10.

[0104] <Cross-cut test: Surface peelability evaluation> To evaluate the surface peelability, a cross-cut test (cross-cut test) was carried out in accordance with JIS K5400. That is, according to JIS K5400, in the center of the molded product (large test piece) obtained above, which is 60 mm long, 60 mm wide, and 3 mm thick, draw orthogonal vertical and horizontal parallel lines at 1 mm intervals with a cutter knife, and 2 The board was cut into a grid pattern so that there were 100 squares (1mm x 1mm) inside. The surface peelability was evaluated using a score of 0 to 10 in the cross-cut test described below in JIS K5400.

[0105] [Table 2]

[0106] <Screw tightening test: Self-tapping breaking torque (unit: N m)> The pellets obtained above were dried at 100°C for 5 hours, and then an injection molding machine (Sumitomo Heavy Industries, Ltd., "SE50DUZ") was used to injection mold the pellets at a cylinder setting temperature of 240 to 260°C and a mold temperature of 60°C to obtain boss hole test pieces for self-tapping tests. The boss hole had a size of 7.5 mm outer diameter, 2.5 mm inner diameter, and 10 mm height and was formed in a plate-shaped portion of 70 mm x 45 mm x 3 mm. A screw (M3×8 P type, thread diameter 3.02 mm, thread root diameter 2.17 mm) was screwed into the boss hole of the obtained test piece with a torque driver, and the torque at which the boss hole caused the female thread to break and result in "screw stripping" was measured, which was taken as the self-tap breaking torque (unit: Nm).

[0107] The above evaluation results are shown in Tables 3 to 5 below. [Table 3]

[0108] [Table 4]

[0109] [Table 5] [Industrial Applicability]

[0110] Molded articles made from the polycarbonate resin composition of the present invention generate little creaking noises (abnormal noises), are free from the problem of surface peeling, and have excellent self-tapping properties. Therefore, they can be suitably used as parts that come into contact with other molded articles or with other molded articles, such as parts in the automotive field, office automation equipment field, home appliances, and electrical and electronic fields, and are particularly suitable for use as automotive interior parts, making them extremely valuable in industry.< / mvr>

Claims

1. A polycarbonate resin (A) containing 55 to 90 parts by mass and a graft copolymer (B) containing an aromatic vinyl monomer component (b1), a vinyl cyanide monomer component (b2), and a diene rubber polymer component (b3) containing 10 to 45 parts by mass of (A) and (B) in total 100 parts by mass, A polycarbonate resin composition comprising 2 to 15 parts by mass of an ethylene-α-olefin copolymer (C) having an MFR (measured at 190°C and 21.18 N) of 0.9 g / 10 min or more, and 0.5 to 10 parts by mass of a styrene-based elastomer (D), wherein the styrene-based elastomer (D) is a hydrogenated styrene-isoprene block copolymer or a polystyrene-polyisobutylene-based elastomer, and the mass ratio (C) / (D) of the contents of (C) and (D) is greater than 1.

2. 2. The polycarbonate resin composition according to claim 1, which has an abnormal noise risk index of 1 to 3 based on VDA 203-206 of the German Automotive Industry Association.

3. 3. The polycarbonate resin composition according to claim 1, wherein the graft copolymer (B) is an ABS resin.

4. A molded article obtained by molding the polycarbonate resin composition according to any one of claims 1 to 3.

5. 5. The molded article according to claim 4, which is an interior part of an automobile.

Citation Information

Patent Citations

  • Polycarbonate composition containing alkenyl aromatic copolymer and lldpe

    JP1983145755A

  • Aromatic polycarbonate resin molding

    JP2014184720A

  • Thermoplastic resin composition and molded article thereof

    JP2018138680A

  • Thermoplastic resin composition and molded product thereof

    WO2015098832A1